The Analysis of Noun Clause Translation in the Novel of The Kill Order - Hasyatun Hasanah (Pioneer: Journal of Language and Literature, 2017)
This research analyzed the noun clause translation in the novel of The Kill Order and its translation novel. The data in this research are in the form of noun clause in The Kill Order novel and its translation novel. The data were collected by reading both novels and taking notes, then the data were analyzed using Spradley’s theory. The data were analyzed through these following steps: domain analysis, taxonomic analysis, componential analysis, and finding cultural value. The result of the research reveals that there were 73 noun clause found in the novel of The Kill Order. This research applied technique of translation theory by Molina and Albir (2002), the researcher found 14 translation techniques with the frequency usage to 133 times. Furthermore, the quality of noun clause translation is qualified with the final assessment of 2.794 by using theory of quality of translation by Nababan et al (2012). The impacts of translation technique to the translation quality are adaptation, amplification, borrowing, compensation, description, discursive creation, established equivalent, linguistic amplification, linguistic compression, literal, modulation, particularization, reduction, and variation are the techniques of translation which produced qualified data of translation. As the follow up, the researcher expects the next researchers to conduct the analysis on translation with other object of research. The researcher also expects the next researchers to identify clause with different relevant theories.